2016
DOI: 10.1016/j.jpor.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fracture resistance between cast, CAD/CAM milling, and direct metal laser sintering metal post systems

Abstract: Co-Cr metal posts fabricated by CCM and DMLS could be an alternative to TC processing in daily clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 20 publications
1
33
0
5
Order By: Relevance
“…Techniques such as stereolithography were implemented to manufacture resin models for posterior manufacture of dental prostheses (crowns and bridges) by conventional process of lost wax castings. Mechanical, chemical, and microstructural properties are evaluated in comparison to new AM technologies, for example, the selective laser melting (SLM) in relation to conventional techniques as lost wax casting [21][22][23]. In this way, the preparation of medical and dental components provides customized final components with high mechanical properties, compared to conventional techniques (see Figure 1) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as stereolithography were implemented to manufacture resin models for posterior manufacture of dental prostheses (crowns and bridges) by conventional process of lost wax castings. Mechanical, chemical, and microstructural properties are evaluated in comparison to new AM technologies, for example, the selective laser melting (SLM) in relation to conventional techniques as lost wax casting [21][22][23]. In this way, the preparation of medical and dental components provides customized final components with high mechanical properties, compared to conventional techniques (see Figure 1) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Beside that all laboratory procedures can be standardized by computerized technology which would minimize the human variations during fabrication of any prosthesis. 10 On the other hand, many studies stated that, the conventional fabrication methods steps necessitate considerable human intervention and materials manipulation that may additionally offer inherent processing shrinkage and/or expansion. This may lead to increased processing errors and inaccuracies which may explain the decreased retention values of conventional dentures in comparison to those of digital dentures in addition to the increase of surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The dental literature comparing microstructural, mechanical and electrochemical properties of casted, milled, and PFB AM metal dental alloys is scarce. 3,39,[42][43][44][45][46][47][48][49][50][51][52] Moreover, the chemical composition of the different Co-Cr and Ti dental alloys vary due to the different manufacturing procedures complicating direct comparisons. 3,44 Different authors reported that the manufacturing method has a strong effect on the metal microstructure.…”
Section: Conventional Versus Am Proceduresmentioning
confidence: 99%